2021
DOI: 10.1136/bmjopen-2020-044483
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, open-label trial to assess the optimal treatment strategy in early diffuse cutaneous systemic sclerosis: the UPSIDE study protocol

Abstract: IntroductionSystemic sclerosis (SSc) is a chronic, autoimmune connective tissue disease associated with high morbidity and mortality, especially in diffuse cutaneous SSc (dcSSc). Currently, there are several treatments available in early dcSSc that aim to change the disease course, including immunosuppressive agents and autologous haematopoietic stem cell transplantation (HSCT). HSCT has been adopted in international guidelines and is offered in current clinical care. However, optimal timing and patient select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The treatment-related mortality of HSCT in the SCOT study was 3% at 54 months and 6% at 72 months 101 , and therefore lower than previously reported (a 2001 phase 1/2 trial reported a procedure-related mortality of 17%) 103 , most likely reflecting careful patient selection and adjustments to the transplantation regime. A key question that is currently being addressed 104 is whether HSCT should be recommended as a first-line therapy as opposed to being reserved for patients who do not respond to immunosuppressant therapies. This difficult decision will be informed by the stratified medicine approach referred to earlier (taking into account advances in our ability to predict those patients most likely to have progressive disease), and by ensuring that individualized care is tailored to patients’ needs and expectations 105 .…”
Section: Best-practice Managementmentioning
confidence: 99%
“…The treatment-related mortality of HSCT in the SCOT study was 3% at 54 months and 6% at 72 months 101 , and therefore lower than previously reported (a 2001 phase 1/2 trial reported a procedure-related mortality of 17%) 103 , most likely reflecting careful patient selection and adjustments to the transplantation regime. A key question that is currently being addressed 104 is whether HSCT should be recommended as a first-line therapy as opposed to being reserved for patients who do not respond to immunosuppressant therapies. This difficult decision will be informed by the stratified medicine approach referred to earlier (taking into account advances in our ability to predict those patients most likely to have progressive disease), and by ensuring that individualized care is tailored to patients’ needs and expectations 105 .…”
Section: Best-practice Managementmentioning
confidence: 99%
“…In order to investigate whether upfront aHSCT is associated with a higher event-free survival compared to conventional immunosuppressive treatment with intravenous cyclophosphamide pulses followed by oral mycophenolate mofetil in patients with early severe dcSSc, the UPSIDE study (UPfront autologous hematopoietic Stem cell transplantation versus Immunosuppressive medication in early DiffusE cutaneous systemic sclerosis; NCT04464434) was recently initiated ( 35 ). The patients in this study have a maximum disease duration of two years, starting from presentation of the first non-Raynaud phenomenon.…”
Section: F-fdg Pet-ct In the Context Of Autologous Stem Cell Transpla...mentioning
confidence: 99%
“…Also, early SCT in patients with limited pulmonary disease may show less impact on present ILD in patients, but could prevent development or progression of ILD, which is currently being investigated in the UPSIDE trial. 43 Severe pulmonary damage pre-treatment could place patients at risk of severe and even fatal treatment complications (an overview of pulmonary complications related to autologous SCT is provided in Table 3). 44 In previous studies pulmonary complications were an important cause of death or organ failure after SCT.…”
Section: Patient Selection and Pulmonary Complicationsmentioning
confidence: 99%
“…Currently the UPSIDE trial is ongoing and investigates upfront SCT in early disease compared with other immunosuppressive therapy and the impact on ILD, using lung function and imaging (automated quantitative HRCT analysis and positron emission tomography) scans to assess changes in the lung after treatment. 43 Also the use of post-transplant MMF in order to prevent (pulmonary) relapse is currently under investigation (NCT01413100). Still, no studies have been done investigating the impact of SCT compared with immunosuppressive medication in the long-term using lung involvement as a primary outcome measure.…”
Section: Implications For Further Researchmentioning
confidence: 99%